Bleeding Risk of Dual Antiplatelet Therapy after Minor Stroke or Transient Ischemic Attack. Issue 3 (10th January 2022) - Wang, Anxin; Meng, Xia; Tian, Xue; Johnston, S. Claiborne; Li, Hao; Bath, Philip M.; Zuo, Yingting; Xie, Xuewei; Jing, Jing; Lin, Jinxi; Wang, Yilong; Zhao, Xingquan; et al.
Abstract : Objective: This study was undertaken to identify the risk of bleeding events and potential risk factors within 90 days in patients who carried CYP2C19 loss‐of‐function alleles and received dual antiplatelet therapy after minor stroke or transient ischemic attack. Methods: A total of 6, 412 patients were enrolled from the CHANCE‐2 (Clopidogrel with Aspirin in High‐Risk Patients with Acute Non‐disabling Cerebrovascular Events II) trial. The main outcome was any bleeding within 90 days defined by the criteria from GUSTO (Global Utilization of Streptokinase and Tissue Plasminogen Activator for Occluded Coronary Arteries). Results: A total of 250 (3.9%) bleeding events were reported, which occurred mainly within the 21 days of dual antiplatelet therapy (200 cases, 3.1%). Minor bleeding of the skin bruises, epistaxis, and gum bleeding were most frequent. Multivariate analysis showed that treatment with ticagrelor‐aspirin compared with clopidogrel‐aspirin was associated with increased bleeding (hazard ratio [HR] = 2.21, 95% confidence interval [CI] = 1.68–2.89, p  < 0.001). Current smoking was associated with a lower risk of bleeding (HR = 0.70, 95% CI = 0.52–0.95, p  = 0.02). Additionally, ticagrelor‐aspirin compared with clopidogrel‐aspirin was associated with higher risk of bleeding in patients aged <65 years (HR = 2.87, 95% CI = 1.95–4.22) and those without diabetes mellitus (HR = 2.65, 95% CI = 1.88–3.73; p for interaction = 0.04 and 0.03, respectively). Interpretation: Bleeding events mostly occurred within the 21‐day dual antiplatelet therapy stage and were generally mild. The risk of bleeding was greater in nonsmoking patients, and was associated with treatment with ticagrelor‐aspirin compared with clopidogrel‐aspirin, particularly in patients aged <65 years and nondiabetic patients. ANN NEUROL 2022;91:380–388